PREDICTIVE SIGNIFICANCE OF ARTERIAL STIFFNESS PARAMETERS IN EVALUATION OF CARDIOMETABOLIC RISK IN OBESITY PATIENTS - O. Yu. Druzhilova; M. A. Druzhilov; T. Yu. Kuznetsova (Российский кардиологический журнал, 2018)
Aim. To evaluate a possibility to apply the arterial stiffness parameters as prediction instrument for cardiometabolic risk stratification in obesity patients.Material and methods. Totally, 274 normotensive males investigated (mean age 44,8±5,0 y.o.), with no clinical signs of cardiovascular disorders and type 2 diabetes, with the SCORE risk <5% and abdominal obesity. The analysis of metabolic risk factors was done, echocardiography, triplex scanning of brachiocephalic arteries, ultrasound assessment of abdominal adipose tissue thickness, bifunctional 24 hour blood pressure monitoring (BP) with assessment of mean 24 hour pulse wave velocity (PWV) in aorta, augmentation index and systolic BP in aorta.Results. The association revealed, of the arterial stiffness parameters with ultrasound marker of visceral obesity, metabolic risk factors and parameters of cardiovascular remodeling. Patients with the PWV in aorta equal or higher than 75th percentile for respective age (77 m/s for 35-45 y.o. and 8,2 m/s for 46-55 y.o.) were different (comparing to the group in general) by higher rate of hypertrophy existence (28,4% vs 11,7%, p<0,001) and diastolic dysfunction of the left ventricle (42,0% vs 16,8%, p<0,001), hypertrophy of the intima-media of carotid artery (50,0% vs 29,2%, p<0,001), carotid atherosclerosis (48,9% vs 18,2%, p<0,001) and higher prevalence of the persons with the relation of abdominal visceral adipose tissue to subcutaneous fat layer >3,0 (56,8% vs 28,1%, p<0,001).Conclusion. The “high” values of PWV in aorta for the respective age diapason (77 m/s for 35-45 y.o. and 8,2 m/s for 46-55 y.o.) witness on higher probability of metabolic disorders and subclinical cardiovascular remodeling, hence the higher cardiometabolic risk. Bifunctional BP 24 hour monitoring with the arterial wall stiffness evaluation in obesity patients is more preferable method making for additional information gather for further risk stratification.